Ανάλυση, σχεδιασμός και κατασκευή μηχανής Stirling υγρών εμβόλων - Ιορδάν, Σταμάτης (Τμήμα Μηχανολόγων Μηχανικών και Επιστήμης και Μηχανικής Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2013)
By completing this thesis, the expected result was to design, to construct and to analyse a liquid Stirling engine. The design was based on various models of researchers of this machine, with minor modifications to better function. The construction was done in collaboration with advisory professor Vassilios Mesaritis, and finally, the experimental operation was performed under the equipment of Cyprus University of Technology at the “Sikopetritis” laboratory facilities. After the completion of the experiments and the analysis of the results, the optimised operating conditions of the engine were made clear which have now opened the way to further research that could increase performance. Once this is achieved, mankind will have access to a more economical and environmentally friendly access to fresh water.
Keywords: Liquid Stirling Engine; Μηχανή Stirling Yγρών Eμβόλων